Experimental and Numerical Characterization of Spot Welded Hybrid Al/CFRP‐Joints on Coupon Level1. Issue 9 (23rd July 2013) - Schmeer, Sebastian; Balle, Frank; Didi, Mirja; Wagner, Guntram; Maier, Martin; Mitschang, Peter
<x xml:space="preserve">Abstract</x> This paper presents investigations on induction and ultrasonic spot welded hybrid Al/CFRP‐specimens. Selected results of welded coupon experiments are discussed. Based on this results detailed FE models are developed and validated by comparison of simulation and experiment. Validated simulations are used to analyze stress states within the hybrid spot welds and to understand the failure progress. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>